PEMANFAATAN JASAD RENIK MIKORIZA UNTUK MEMACU PERTUMBUHAN TANAMAN HUTAN - J. M. Sri Hardiatmi (Innofarm:Jurnal Inovasi Pertanian, 2008)
ABSTRACT In order to rehabilitate forest with reboisation, Indonesian forestry department has established 6,2 millions acre of Industrial plants forest located on endanger land and infertile forest. The bad condition of the soil, which will be used for HTI, will raise problem for the growth of the plants themselves. The problem rises because the plants need nutrition in a great number and an immediate term. Generally, nutrition is given easily and immediately by giving artificial fertilizer such as; Urea, KCl, SP-36, etc. However, this method has some weaknesses. Firstly, it costs greater number of money. On the other hand, it arouses another environment problem because the fertilizers are easily washed so that it will cause eutrification. Another safer approach is needed based on the problem arose by the method of giving fertilizer. Following biosfer process is one of the naturally method which is good to increase the growth of the plants. There is also a proper and suitable alternative option by using microorganism. Microorganisms which live in the soil play important roles in the process of organic decomposition, so that it can be used by the plants to support their growth. Some of the microorganisms form micoriza fungus. They make mutualism symbiosis with various kinds of plants in the forest. Those symbioses increase or alter the existence of nutrition in the soil, so that it can be used by the plants. By this special ability, micoriza microorganism becomes very helpful in increasing the growth of the plants. On the other hands, it also protects the plants from the pathogen attack and increased the survival ability of the plants themselves from the dryness. This method can be done by giving inoculums of micoriza during the seeds and after planting on the field. This method is expected to be the helpful solution to in setting the growth of Industrial Plant forest and other kinds of forest. Key words: Forestry plants, Micoriza microorganism, mutualism symbiosis.